Desenvolvimento de sensores nanoestruturados para análise de tetraciclina em leite - Scagion, Vanessa Priscila (2015)
This work deals with the application of two arrays of sensors composing an electronic tongue for the quality evaluation of UHT-type milk, with the specific aim of detecting the antibiotic tetracycline in this dairy product. The electronic tongue device was made up by sensing units composed by gold interdigitated electrodes assembled onto glass substrates. Polyamide 6 (PA6) nanofibers and PA6/polyaniline (PAni) blends were deposited on the electrodes via the electrospinning technique. The nanofibers were characterized by means of scanning electron microscopy (SEM), X-ray diffraction (XRD), FTIR spectroscopy, Raman spectroscopy, differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA/DTG). The electronic tongue measurements were carried out using an impedance analyzer to collect capacitance and resistance data at 1 KHz. As chemometric tool we employed the Principal Component Analysis (PCA) technique to verify the efficiency of the electrospinning nanofibers-based electronic tongue in distinguishing different types of milk, as well as those contaminated by tetracycline. The results showed that the use of PAni for obtaining polymer blend fibers caused some small changes on the physical chemical properties compared to the neat PA6 fiber. However, PAni addition allowed a great reduction on the fiber diameter. Our results demonstrated that the electronic tongue system is a potential methodology to be used for classifying milk samples, in terms of fat content and quality regarding the presence of antibiotic tetracycline. The electronic tongue system system was able to detect milk samples contaminated up to 1ppb of tetracycline, regardless of milk fat content.